International trade regulation and sustainable development: An outlook - Karl Steininger (Intereconomics, 1996)
Sustainable development at both the national and the global level is increasingly acknowledged to be dependent upon the international trade system. The WTO Agreements and the continuing discussion in the WTO Committee on Trade and Environment are therefore examined here in the light of principles put forward by the International Institute for Sustainable Development. The current shortcomings in the WTO are analysed and some possible cornerstones for future WTO development indicated.
Keywords: 330; WTO